A influência da estrutura do hábitat sobre a composição da avifauna em praças públicas - Marques, Renata Leal (2010)
There is a recognized increase of landscapes dominated by human populations that can t be ignored in the search for biodiversity conservation. The knowledge of the impacts that urbanization can have on bird communities can allow the identification of important tools to better plan of urban habitats so that this group can survive in these environments. The vegetation present at the cities, mainly in public open spaces such as squares, plays an important role by increasing biodiversity. Therefore, we evaluated the responses of bird communities to habitat structure, to location and to human disturbance at 40 squares of different regions of Uberlândia, MG. The birds observation was carried out by visual records with detailed scanning across the square and the surrounding streets, from March to November 2009, between 6:30am and 13:00pm. The number of species and individuals were recorded. The substrate and the vertical stratum used, the behavioral activity performed and the resource exploited by birds were recorded. In each square were measured the total area, the richness and the number of plant individuals classified in heights 0.5-6.0 meters and above 6 meters, the proportion of ground cover, the proportion of surrounding cover vegetation, distance to the city central point, distance to the periphery and to the native vegetation remnant closer. Moreover, were recorded the number of residential and public buildings in the immediate surroundings of the square and the number of pedestrians, vehicles and pets. Were performed 412 hours of observation and 121 bird species were recorded at the squares, distributed in 14 orders, 37 families and 101 genera. The order Passeriformes was more representative and the family Tyrannidae was richer. We obtained 12 new species records for the urban area and 15 species had only one individual during the study period. The acumulation curve indicated that number of recorded species is close to the real number of bird community found in town squares. The most abundant species at squares were Zenaida auriculata (448.63), Passer domesticus (254.50) and Patagioenas picazuro (238.25). The squares have from 23 to 65 species of birds and showed high similarity. The birds used mainly trees and the upper strata, using the squares especially for shelter, food and reproduction. Birds richness at squares was correlated to plant richness and to number of plants individual above 6.0 meters, to proportion of surrounding cover vegetation the square, to distance to the native vegetation remnant, to distance to city center and to number of pedestrians. The composition of birds and the foraging and reproduction activities correlated with the characteristics of the squares vegetation. In addition, the reproduction was related to distance to city central point, to proportion of non-paved substratum and to number of pedestrians. Thus, squares, especially those with more complex vegetative structure, can provide important habitats for the maintenance of a varied avifauna in the urban environment.